2007
DOI: 10.1117/12.711781
|View full text |Cite
|
Sign up to set email alerts
|

Mask enhancement using an evanescent wave effect

Abstract: State of the art lithography is continually driven to resolve increasingly smaller features, forcing k 1 values for lithography processes ever lower. In order to image these difficult features with reliable fidelity, lithographers must increasingly use Resolution Enhancement Techniques (RETs). One such technique that is proposed in this paper uses small, sub-wavelength grooves placed in close proximity to an aperture. These sub-wavelength grooves create evanescent fields bound to the surface between the absorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In this case, high refractive solid immersion lens is combined with conventional far- propagating modes [104,105]. The use of evanescent fields in enhancing transmission through aperture on a screen has been demonstrated by researchers [106]. The authors have suggested that an array of sub-wavelength features can be generated the direct interference of the evanescent modes and enhancement is due to the propagating modes traveling through an aperture.…”
Section: Evanescent Wave Lithographymentioning
confidence: 99%
“…In this case, high refractive solid immersion lens is combined with conventional far- propagating modes [104,105]. The use of evanescent fields in enhancing transmission through aperture on a screen has been demonstrated by researchers [106]. The authors have suggested that an array of sub-wavelength features can be generated the direct interference of the evanescent modes and enhancement is due to the propagating modes traveling through an aperture.…”
Section: Evanescent Wave Lithographymentioning
confidence: 99%